2021
DOI: 10.1016/j.jbc.2021.100489
|View full text |Cite
|
Sign up to set email alerts
|

Is γ-secretase a beneficial inactivating enzyme of the toxic APP C-terminal fragment C99?

Abstract: Genetic, biochemical, and anatomical grounds led to the proposal of the amyloid cascade hypothesis centered on the accumulation of amyloid beta peptides (Aβ) to explain Alzheimer's disease (AD) etiology. In this context, a bulk of efforts have aimed at developing therapeutic strategies seeking to reduce Aβ levels, either by blocking its production (γ- and β-secretase inhibitors) or by neutralizing it once formed (Aβ-directed immunotherapies). However, so far the vast majority of, if not all, clinical trials ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 232 publications
3
31
0
Order By: Relevance
“…Upon β-secretase-mediated (BACE1) cleavage of the β C-terminal fragment (β-CTF/C99) from APP, the γ-secretase complex produces the Aβ peptides associated with AD. Importantly, β-CTF has been shown to accumulate before Aβ peptides aggregate in vivo and, therefore, it is proposed to be an early and critical factor for initiating neurodegenerative processes and cognitive decline in AD [71][72][73]. Our data demonstrate strongly reduced levels of both β-CTF/C99 and Aβ monomers in insoluble protein fractions from Ttg mice (using 6E10 antibody) supporting the beneficial outcome on plaque burden upon astrocytic IKK2/NF-κB activation.…”
Section: Discussionsupporting
confidence: 63%
“…Upon β-secretase-mediated (BACE1) cleavage of the β C-terminal fragment (β-CTF/C99) from APP, the γ-secretase complex produces the Aβ peptides associated with AD. Importantly, β-CTF has been shown to accumulate before Aβ peptides aggregate in vivo and, therefore, it is proposed to be an early and critical factor for initiating neurodegenerative processes and cognitive decline in AD [71][72][73]. Our data demonstrate strongly reduced levels of both β-CTF/C99 and Aβ monomers in insoluble protein fractions from Ttg mice (using 6E10 antibody) supporting the beneficial outcome on plaque burden upon astrocytic IKK2/NF-κB activation.…”
Section: Discussionsupporting
confidence: 63%
“…Lastly, we show that TDP43 219 can interact with the BAG6-recruited Ub-ligase, RNF126 and is associated with RNF126-catalyzed ubiquitylation ( Figure 5 ). In support of a general function in preventing the aggregation of neurodegeneration-associated fragments, we found that BAG6 also interacts with and solubilizes the amyloidogenic Aβ peptide and the β-secretase generated C-terminal fragment of the amyloid precursor protein, βCTF, involved in AD pathology ( Pulina et al., 2020 ; Checler et al., 2021 ). Our data support a model ( Figure 6 D) whereby limited proteolysis during pathological conditions generate proteolytic fragments containing exposed hydrophobicity.…”
Section: Discussionmentioning
confidence: 62%
“…The physiological significance of the presented two-substrate-mechanism will be summarized around five closely related observations from different studies of changes in γ-secretase activity in Alzheimer’s disease. Development of early diagnostic methods and effective drug-design strategies depends on our ability to connect observations from different enzyme-based, cell-based, animal-based, and clinical studies of Alzheimer’s disease [3,5,7,9,10,29].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we expand some of the earlier enzyme activity studies using advanced computational methods for the analysis of the interaction between γ-secretase, β-secretase, and C99-βCTF-APP [27,28]. Specifically, we analyze proposals that pathogenic events can be attributed to the accumulation of C99-βCTF-APP and Aβ molecules of different lengths [10,11,13,29].…”
Section: Introductionmentioning
confidence: 99%